National Branding Pariwisata Labuan Bajo Pada Konferensi Tingkat Tinggi (KTT) ASEAN Ke-42 - Fauzi, Reza; Witari, Denik Iswardani (Universitas Al Azhar Indonesia, 2023)
In Labuan Bajo, there are a number of attractions that could entice visitors from the archipelago and outside. Westmost point of Flores Island is in East Nusa Tenggara (NTT). Labuan Bajo is one of the five Super Priority Tourism Destinations (DPSP) that the government has chosen to as the venue for the 42nd ASEAN Summit. Nation branding generally refers to a country’s strategy to convey a particular image of itself beyond its borders to achieve certain beneficial goals. The notion is associated with the existence of a